Therapeutic Music in the Aeromedical Transport of Critically Ill Patients: Intervention to Reduce Flight Stressors (Global Journal of Medical Research, 2022)
Abstract-Therapeutic music is one of the strategies widely adopted as a complementary therapy proven by its relevance as a strategy to reduce pain decrease the level of anxiety and increase adherence to treatment especially in critically ill hospitalized patients The application of complementary practices in critically ill patients has been introduced in many Intensive Care Units ICU as their benefits are evidenced both in biopsychosocial well-being and in the spiritual sphere This work is a survey of articles whose objective was to characterize the scientific production on the application of Music Therapy The main search source was in the databases indexed in the Biblioteca Virtual de Sa de BVS and Scientific Electronic Library Online SciELO In order to reduce the damage caused by painful procedures and the permanence in an exhausting environment such as the ICU full of alarms lights and other noises many professionals seek a way to humanize through various integrative and non-pharmacological therapies Among these we find in the literature a varied range such as breastfeeding music therapy laughter therapy with clowns use of sucrose among others And through the analysis of the highly technological environment such as planes and helicopters that provide safety to airborne critical patients we realized that this alternative can humanize this environment and bring possible results such as reduction of flight stressors This work is just the basis for the next phase of the research that will be extended with practical application on Helisul flights
Keywords: air medical transport; music therapy; integrative therapies